2021
DOI: 10.3389/fnins.2021.685977
|View full text |Cite
|
Sign up to set email alerts
|

Localized Modification of Water Molecule Transport After Focused Ultrasound-Induced Blood–Brain Barrier Disruption in Rat Brain

Abstract: Interstitial solutes can be removed by various overlapping clearance systems, including blood–brain barrier (BBB) transport and glymphatic clearance. Recently, focused ultrasound (FUS)-induced BBB disruption (BBBD) has been applied to visualize glymphatic transport. Despite evidence that FUS–BBBD might facilitate glymphatic transport, the nature of fluid movement within the sonication region is yet to be determined. In this study, we sought to determine whether FUS–BBBD may facilitate the local movement of wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 76 publications
1
14
0
Order By: Relevance
“…When analyzing the MR images, Evans blue dye, and histology based on the cavitation dose, BBBD was observed. Indeed, we studied the long-term effects of BBBD in our previous study, showing that the brain was restored to a normal state within 72 h after BBBD [ 53 ]. Furthermore, our ultrasound parameters were derived based on previous results using a 1 MHz FUS transducer.…”
Section: Discussionmentioning
confidence: 99%
“…When analyzing the MR images, Evans blue dye, and histology based on the cavitation dose, BBBD was observed. Indeed, we studied the long-term effects of BBBD in our previous study, showing that the brain was restored to a normal state within 72 h after BBBD [ 53 ]. Furthermore, our ultrasound parameters were derived based on previous results using a 1 MHz FUS transducer.…”
Section: Discussionmentioning
confidence: 99%
“…The microbubble solution was diluted 50-fold in saline and injected intravenously at a dose of 10 μL/kg. Microbubbles with less than two hours of activation were used (manufacturer’s guidelines <12 h) to ensure a similar level of microbubble concentration among all experiments [ 12 ]. The sonication intensities were (1) sham, (2) 1.5 MPa, (3) 1.8 MPa, and (4) 2.0 MPa.…”
Section: Methodsmentioning
confidence: 99%
“…Sonication was applied synchronously to an in nous injection of microbubbles (Definity, Lantheus Medical Imaging, N.Billerica which consisted of C3D8 gas encapsulated by an outer phospholipid shell. The micr ble solution was diluted 50-fold in saline and injected intravenously at a dose of 10 Microbubbles with less than two hours of activation were used (manufacturer's lines <12 h) to ensure a similar level of microbubble concentration among all exper [12]. The sonication intensities were (1) sham, (2) 1.5 MPa, (3) 1.8 MPa, and (4) 2.0 M (A) (B)…”
Section: Focused Ultrasound Sonicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Below this range (for instance, at a pressure of 0.28 MPa), the uptake of nanoclusters was negligible in glioblastoma, while having no significant difference at 0.61, 0.72, and 0.85 MPa, respectively ( 60 ). Recently, it has also been shown that with increasing pressure, the diffusion of water molecules increases due to the upregulation of aquaporin-4 ( 75 ). Moreover, these parameters also determine whether the therapeutics uptake will be early/fast or slow/late ( 8 ).…”
Section: Low-intensity Focused Ultrasoundmentioning
confidence: 99%